DAKWAH KOMUNITAS MUHAMMADIYAH DI KAWASAN PELACURAN KOTA SURABAYA - Mukayat, Al-amin (Universitas Muhammadiyah Surabaya, 2021)
The Surabaya City Government successfully curtailed prostitution activities by closing down red-light districts such as Dupak Bangunsari/Kremil and Dolly. However, these closures have left several issues for former sex workers still residing in these areas. In this context, Muhammadiyah Surabaya plays a key role in the guidance and empowerment of former sex workers. This research reveals the community preaching strategies of Muhammadiyah, including enhancing faith, providing entrepreneurial skills, intensive preaching in areas still practicing prostitution, micro-economic development, health counseling for those affected by sexually transmitted diseases, repurposing former prostitution locations, and psychological support through counseling. These strategies aim to provide sustained reinforcement and guidance to former sex workers, addressing their vulnerable and weakened psychological, sociological, and economic conditions post-closure. A qualitative approach is employed in this research through observation, interviews, and literature review. The research findings indicate Muhammadiyah's success in providing holistic support to former sex workers, imparting skills and knowledge, and assisting them in developing micro-economies to enhance their well-being. Keywords: Muhammadiyah Community Preaching, Surabaya City Prostitution Area